[PP.03.04] PREVALENCE AND PROGNOSIS OF ELECTROCARDIOGRAPHIC ABNORMALITIES IN NORMOTENSIVE AND HYPERTENSIVE INDIVIDUALS. (September 2016) - Lehtonen, A.; Puukka, P.; Varis, J.; Porthan, K.; Tikkanen, J.; Nieminen, M.; Huikuri, H.; Anttila, I.; Nikus, K.; Kähönen, M.; Jula, A.; Niiranen, T.
Abstract : Objective: Our objective was to define the prevalence and prognosis of electrocardiographic (ECG) abnormalities in hypertensive individuals. From a clinical point of view, this study could help physicians to take better advantage of ECG in the risk assessment of hypertensive patients. Design and method: ECG, blood pressure and other cardiovascular risk factors were recorded in a nationwide population sample of 5800 Finns. The presence of 15 ECG abnormalities was evaluated. Participants were divided into categories by blood pressure and followed for coronary heart (CHD) and cardiovascular disease (CVD) events. Results: Mean follow-up was 10.4 ± 2.2 years. The age- and gender-adjusted prevalence rates of ECG abnormalities were generally higher in the hypertensive participants than in normotensives. In multivariable-adjusted Cox models, the following ECG abnormalities predicted CHD in hypertensives: Left ventricular hypertrophy (LVH) by Sokolow-Lyon criteria (Hazard ratio (HR), 1.47; 95% CI, 1.07–2.01; P = 0.02), LVH with ST-depression and negative T wave (ST/T changes) (HR, 2.31; 95% CI, 1.20–4.43, P = 0.01), ST/T changes (HR, 2.12; 95% CI, 1.34–3.36; P = 0.001), positive T wave in lead aVR (AVRT+) (HR, 1.74; 95% CI, 1.15–2.64; P = 0.009) and poor R-wave progression (HR, 2.02; 95% CI, 1.27–3.22; P = 0.003). These ECG abnormalities were also significant predictors of CVD in hypertensives (P < 0.03 for all). LVH and ST/T changes were the only ECG abnormalities that improved the model discrimination in hypertensives. Non-specific intraventricular conduction delay (IVCD) predicted CVD in the whole population (HR, 1.50; 95% CI, 1.06–2.13; P = 0.02). Prolonged QT interval, abnormal P-wave indices, left axis deviation and early repolarization pattern were not associated with CHD or CVD. Conclusions: We conclude that ECG abnormalities are highly prevalent in hypertensive individuals. LVH is still the cornerstone of cardiovascular risk assessment in hypertensive patients. However, the additional assessment of ST/T changes, AVRT+ and poor R-wave progression in ECGs could improve risk prediction in hypertensives.